Facile synthesis of spherical covalent organic frameworks as stationary phases for short-column liquid chromatography. Issue 61 (14th July 2021) - Zheng, Qiong; He, Yanting; Ma, Wende; Wu, Yijing; Chen, Zihan; Wang, Ran; Tong, Wei; Lin, Zian
Abstract : Micron-sized spherical covalent organic frameworks (SCOFs ) were simply synthesized and used for the first time as stationary phases for the separation of various small molecules and protein digests using short-column liquid chromatography. Abstract : Micron-sized spherical covalent organic frameworks (SCOFs ) with tunable sizes, narrow size distribution, and significant mono-dispersity were simply synthesized at room temperature. Thanks to their high specific surface areas, high chemical and mechanical stability, the SCOFs were used for the first time as stationary phases for high-efficiency separation of various small molecules and protein digests via short-column liquid chromatography.